2022
DOI: 10.1021/acs.jpca.1c10828
|View full text |Cite
|
Sign up to set email alerts
|

Through-Bond-Driven Through-Space Interactions in a Fullerene C60 Noncovalent Dyad: An Unusual Strong Binding between Spherical and Planar π Electron Clouds and Culmination of Dyadic Fractals

Abstract: Hydrogen-bond-induced π-depletion as a criterion for π-stacking, a configurationally unique noncovalent strategy enabled an unconventional strong binding between the spherical N-fulleropyrrolidine (NFP) and the planar distributions of π electron clouds of three substituted pybates to form noncovalent fulleropyrrolidino-4-(pyrenyl) butanoate dyads of large computed interaction energies, varying between 37.49 and 44.93 kcal/mol. The geometrical distortion/bending of the alkyl tail of pybate in the noncovalent dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“… 42 A thorough literature review showed that the higher the stabilization energy the stronger the interaction between the donor orbital and acceptor orbital and the stronger the strength of adsorption of the sensing materials. 43 The second-order perturbation energy of the studied doped MoS 2 monolayer and its interaction with NH 3 gas was estimated using eqn (6) 44 where q i is the donor orbital occupancy, ε i , and ε j represent the diagonal elements and F ( i , j ) stands for the off-diagonal elements of the Fock matrix.…”
Section: Resultsmentioning
confidence: 99%
“… 42 A thorough literature review showed that the higher the stabilization energy the stronger the interaction between the donor orbital and acceptor orbital and the stronger the strength of adsorption of the sensing materials. 43 The second-order perturbation energy of the studied doped MoS 2 monolayer and its interaction with NH 3 gas was estimated using eqn (6) 44 where q i is the donor orbital occupancy, ε i , and ε j represent the diagonal elements and F ( i , j ) stands for the off-diagonal elements of the Fock matrix.…”
Section: Resultsmentioning
confidence: 99%
“…SPE calculations were carried out using the 6-311+G(d,p) basis set at B3LYP, M06-2X, and ωB97X-D functionals. 35 The polarizable continuum model 36–38 (PCM) implemented in the Gaussian 16 program package was used to incorporate the solvation (THF) effect at B3LYP, M06-2X, and ωB97X-D theory levels, the last two being hybrid long-range separated functionals, which take care of empirically-corrected dispersion interactions for studying structures with non-covalent interactions of the catalyst C 60 -substrate type. In separate sets of calculations, relative free energies were obtained using the B3LYP-D3 level of theory to incorporate dispersion correction for all the intermediates in Scheme 1A and B, the details of which are provided in Tables S1 and S2 (see ESI†).…”
Section: Computational Detailsmentioning
confidence: 99%